The Social Construction of Reality / A Treatise in the Sociology of Knowledge - Berger Peter L.; Luckman Thomas (Penguin Books, 1991)
A general and systematic account of the role of knowledge in society aimed to stimulate both critical discussion and empirical investigations. Preface, Introduction, The Problem of the Sociology of Knowledge, The Foundations of Knowledge in Everyday Life, The Reality of Everyday Life, Social Interaction in Everyday Life, Language and Knowledge in Everyday Life, Society as Objective Reality, Institutionalization, Legitimation, Society as Subjective Reality, Internalization of Reality, Internalization and Social Structure, Theories about Identity, Organism and Identity, The Sociology of Knowledge and Sociological Theory, Notes, Indexes.